Sharing hidden know-how : how managers solve thorny problems with the knowledge jam - Pugh, Katrina (San Francisco, CA : Jossey-Bass, 2011)
'One of the great management ideas of the last fifteen years has been to make use of the knowledge that an organization has already learned. This book's five-step process, which the author calls Knowledge Jam, shows how to set the direction, foster the correct tone, conduct a knowledge capture event, and integrate this knowledge into the organization. It also introduces conversation practices for participants to effectively co-create knowledge and discover context. Rich with case studies, how-to templates, and adaptations, this book is ideal for external consultants, internal facilitators and leaders'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Knowledge management; Organizational learning; Organizational learning -- Management